Rational design and performance prediction of organic photosensitizer based on TATA+ dye for hydrogen production by photocatalytic decomposition of water - Yu, Yuening; Yang, Zhenqing; Xia, Yuhong; Lv, Yuzhuo; Zhang, Wansong; Lin, Chundan; Shao, Changjin (Frontiers in Chemistry, 2023)
In comparison to metal complexes, organic photosensitive dyes employed in photocatalytic hydrogen production exhibit promising developmental prospects. Utilizing the organic dye molecule TA+0 as the foundational structure, a series of innovative organic dyes, denoted as TA1-1 to TA2-6, were systematically designed. Employing first-principles calculations, we methodically explored the modifying effects of diverse electron-donating groups on the R1 and R2 positions to assess their application potential. Our findings reveal that, relative to the experimentally synthesized TATA+03, the TA2-6 molecule boasts a spatial structure conducive to intramolecular electron transfer, showcasing the most negative reduction potential (Ered = −2.11 eV) and the maximum reaction driving force (△G02 = −1.26 eV). This configuration enhances its compatibility with the reduction catalyst, thereby facilitating efficient hydrogen evolution. The TA2-6 dye demonstrates outstanding photophysical properties and a robust solar energy capture capacity. Its maximum molar extinction coefficient (ε) stands at 2.616 × 104 M−1·cm−1, representing a remarkable 292.8% improvement over TATA+03. In conclusion, this research underscores the promising potential of the TA2-6 dye as an innovative organic photosensitizer, positioning it as an efficacious component in homogeneous photocatalytic systems.